The variables that could influence remission period in alcohol dependence - Özgür İlhan, İnci and Demirbaş, Hatice and Yolaç Yarpuz, Aslı and Doğan, Yıldırım B. (Journal of Dependence, 2003)
Objective: In the present study, it was aimed to determine variables that might influence process of remission in a group of alcohol dependent patients. Method: All of the hospitalized patients and outpatients staying abstinent for at least 3-month periods were included in the study. Sociodemographic characteristics, information about alcohol use and treatment histories of patients were taken as independent variables. Duration of abstinence was taken as 6-month periods for statistical analysis. Results: Patients who reported problems with work-place as a reason for application for treatment were more likely to be abstinent for longer periods. A significant relationship was found between a history of group therapy and duration of remission. Conclusion: It can be suggested that problems with work-environment may be determinant for alcohol dependent patients in terms of motivation for treatment and positive prognosis. Moreover, it is proposed that interper-sonally oriented interactional group therapy is an effective treatment method considering duration of abstinence in alcohol dependent patients.